Korean editors’ and researchers’ experiences with preprints and attitudes towards preprint policies - Hyun Jung Yi; Sun Huh (Science Editing, 2021)
Purpose This study investigated editors’ and researcher’s experiences with preprints and their attitudes towards preprint policies in Korea. Methods From December 30, 2019 to January 10, 2020, a Google Forms survey was mailed to members of the Korean Council of Science Editors and the Korean Federation of Science and Technology Societies. The 16 survey items included two demographic items, six items on experience with preprints, five 5-point Likert-scale items on attitudes towards preprints, and three items on advantages and disadvantages. Results Out of 365 respondents, 56 had deposited their manuscripts on preprint servers, while 49 stated that they allowed preprints in their journals. More than half of the respondents expressed favorable attitudes towards prioritizing preprint deposition, promotion of open access, rapid feedback on preprints, earlier citations, and evidence of research work. Responders in engineering had more experience with the concept of preprints, and were more likely to have heard about preprint servers and preprint deposition by other researchers, than those in medicine. Half of the editors disagreed with the need for preprints, for reasons including a lack of scientific integrity, stealing ideas/scooping data, priority issues regarding research ideas, and copyright problems. Conclusion The above results showed that preprints are still not actively used in Korea. Although experiences with preprints were not widespread, more than half of the respondents showed favorable attitudes towards preprints. More of a consensus should emerge for preprint policies to be accepted by editors in Korea.